2002
DOI: 10.2527/2002.8051195x
|View full text |Cite
|
Sign up to set email alerts
|

Online evaluation of a commercial video image analysis system (Computer Vision System) to predict beef carcass red meat yield and for augmenting the assignment of USDA yield grades. United States Department of Agriculture

Abstract: Objective quantification of differences in wholesale cut yields of beef carcasses at plant chain speeds is important for the application of value-based marketing. This study was conducted to evaluate the ability of a commercial video image analysis system, the Computer Vision System (CVS) to 1) predict commercially fabricated beef subprimal yield and 2) augment USDA yield grading, in order to improve accuracy of grade assessment. The CVS was evaluated as a fully installed production system, operating on a full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 0 publications
4
25
1
1
Order By: Relevance
“…LI et al, (1997) showed that brittleness of meat could be determined by vision texture analysis. Similarly, investigations have shown this method can be used to analyze meat, determine marbling score and evaluate MLD area (NEWMAN, 1984;KUCHIDA et al, 1991;SHACKELFORD et al, 1998;SHIRANITA et al, 2000;KARNUAH et al, 2001;CANNELL et al, 2002;TEIRA et al, 2003). BOZKURT et al, (2006) used digital image analysis technology regarding prediction of body weight from body measurements in beef cattle.…”
Section: Introductionmentioning
confidence: 99%
“…LI et al, (1997) showed that brittleness of meat could be determined by vision texture analysis. Similarly, investigations have shown this method can be used to analyze meat, determine marbling score and evaluate MLD area (NEWMAN, 1984;KUCHIDA et al, 1991;SHACKELFORD et al, 1998;SHIRANITA et al, 2000;KARNUAH et al, 2001;CANNELL et al, 2002;TEIRA et al, 2003). BOZKURT et al, (2006) used digital image analysis technology regarding prediction of body weight from body measurements in beef cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Different VIA systems have been studied outside the UK, mostly in beef cattle, to predict on-line carcass value and by the use of additional systems also aspects of meat eating quality (e.g. Cannell et al, 2002;Shackelford et al, 2003;Steiner et al, 2003;Vote et al, 2003, Allen & Finnerty, 2001Allen, 2005). While there are also a few studies on instrumental grading of lamb carcasses (Hopkins, 1996, Stanford et al, 1998, Brady et al, 2003Hopkins et al, 2004, Cunha et al, 2004, none of them had been applied to UK conditions for lamb carcasses until very recently.…”
Section: Muscle Density and Intramuscular Fat (Imf)mentioning
confidence: 99%
“…For detection of quality degree of beef carcass, researches in this area began in the early 80s. Many people have studied on the detection of beef marbling, muscle color and fat color by computer vision [6]- [8]. Some previous research show that only few people had carried out the research on image automated segmentation algorithm for cartilage and bone areas and the automatic identification of skeletal maturity grade.…”
Section: Introductionmentioning
confidence: 99%